Favorite fairy tales told in Germany - Haviland, Virginia, 1911-1988.; Grimm, Jacob, 1785-1863.; Grimm, Wilhelm, 1786-1859.; Paterson, Diane, 1946- (1994)
Seven well-known German tales: The Frog Prince, The Elves and the Shoemaker, Rapunzel, The Cat and the Mouse in Partnership, Rumpelstiltskin, Hansel and Gretel, and The Bremen Town Musicians.
Keywords: Fairy tales -- Germany; Folklore -- Germany -- Juvenile literature